Byphenyl Hydrazone@SiO2 Composite: Synthesis and Evaluation of a New Chemosensor System for the Detection of Cu2+ - Guntero, Vanina Alejandra (2019)
In the present work a byphenyl hydrazone/SiO2 composite was synthetized by a simple procedure. First, the mesoporous SiO2 and the byphenyl hydrazone ligand were prepared. To prepare the composite, the mesoporous silica and the ligand were dispersed in ethanol/water by a microwave assisted process. Then, the composite was characterized by different techniques to evaluate its chemosensor properties. The physicochemical characterization of the composite confirmed the selectivity and sensitive capacity to detect Cu+2 ions.